Testing between Competing Models of Wage and Employment Determination in Unionized Markets - MaCurdy, Thomas E.; Pencavel, John H. (Journal of Political Economy, 1986)
Two models of wage and employment determination in unionized markets are routinely exposited. According to one, wage and employment outcomes are on the firm's labor demand curve; according to the other, wages and employment are on the partie' contract curve. This paper spells out an empirical procedure that discriminates between these two models and applies this procedure to the particular case of the newspaper industry and the International Typographical Union. The labor demand curve model is inconsistent with our data, while the contract curve model comes closer to describing our observations.